Morphology and surface analyses for CH3NH3PbI3 perovskite thin films treated with versatile solvent–antisolvent vapors. Issue 29 (17th May 2021) - Awol, Nasir; Amente, Chernet; Verma, Gaurav; Kim, Jung Yong
Abstract : Organometal halide perovskite (CH3 NH3 PbI3 ) semiconductors have been promising candidates as a photoactive layer for photovoltaics. Abstract : Organometal halide perovskite (CH3 NH3 PbI3 ) semiconductors have been promising candidates as a photoactive layer for photovoltaics. Especially for high performance devices, the crystal structure and morphology of this perovskite layer should be optimized. In this experiment, by employing solvent–antisolvent vapor techniques during a modified sequential deposition of PbI2 –CH3 NH3 I layers, the morphology engineering was carried out as a function of antisolvent species such as: chloroform, chlorobenzene, dichlorobenzene, toluene, and diethyl ether. Then, the optical, morphological, structural, and surface properties were characterized. When dimethyl sulfoxide (DMSO, solvent) and diethyl ether (antisolvent) vapors were employed, the CH3 NH3 PbI3 layer exhibited relatively desirable crystal structures and morphologies, resulting in an optical bandgap ( E g ) of 1.61 eV, crystallite size ( t ) of 89.5 nm, and high photoluminescence (PL) intensity. Finally, the stability of perovskite films toward water was found to be dependent on the morphologies with defects such as grain boundaries, which was evaluated through contact angle measurement.